EFEKTIFITAS MODEL PEMBELAJARAN THINKING ALOUD PAIR PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Yohanes Azka, Yohanes Azka; Kartikasari, Ika; Suryati, Suryati; Asyhar, Rayandra (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This study examined the low mathematical problem-solving ability of grade VIII students at SMP N 13 Merangin, where only 12 out of 35 students achieved the Minimum Completeness Criteria (KKM), far below the classic achievement target of 70%. In addition, student learning outcomes are still relatively low at 31.18%, completely because the learning method is still centered on teachers. This study aims to describe the mathematical problem-solving ability of students using the Thinking Aloud Pair Problem Solving (TAPPS) learning model better than conventional learning. An experimental method was used, with 124 grade VIII students as the population and simple random sampling to determine class VIII B as the control group and VIII C as the experimental group. Data was collected using essay questions on algebraic simplification. The normality test using the Kolmogorov-Smirnov formula and the homogeneity test with the Hartly test (F-test) showed normal and homogeneous distributed data. The hypothesis test using the t-test produces a calculation value of t-calculate. =2.65 is greater than, =1.67, meaning, Accepted. This shows that the mathematical problem-solving ability taught using the TAPPS model is better than the conventional method.